Les conditions de la résilience des services urbains parisiens par l’apprentissage collectif autour des interdépendances - Marie Toubin (Éditions en environnement VertigO, 2013)
The resilience concept seems to be a promising one for a better risk management in cities. And yet, even the interesting capacities related to the concept: absorption, adaptation and learning are difficult to implement at an operational level. Thus, our research is much more concerned in building the conditions for a resilient city rather than characterizing and assessing urban resilience. To do so, we develop a collaborative approach with Paris’ urban services managers in order to increase their knowledge and their communication given that urban services are important both in risk propagation and in business continuity. We have collected data concerning urban services interdependencies and gathered urban managers in three collaborative workshops. The workshops have contributed to improve the global knowledge concerning interdependencies management and assess their impacts on urban systems in case of floods. It demonstrates the complexity of interactions and the criticality of urban services continuity in the resilience of Paris to the 100-year flood risk. Different strategies in managing power distribution, public transportation, waste collection, water supply or telecommunications lead to different consequences on other urban services and on the city’s capacity to respond to and recover from floods. Then the collaborative approach answers this need for more communication and coordination between interdependent stakeholders. It should also contribute to build a more integrated response and improve Paris’ resilience.